Self-Esteem and Happiness as Predictors of School Teachers’ Health: The Mediating Role of Job Satisfaction - Benevene, Paula; Ittan, Maya M.; Cortini, Michela (Frontiers in Psychology, 2018)
Background: A wealth of cross-sectional studies show consistent positive relationships between teachers’ happiness and self-esteem on one hand, and health, on the other, which calls for additional research in order to disentangle cause and effect between the two, and to find potential mediators. Aims: To investigate the mediating role played by job satisfaction between teachers’ happiness and self-esteem and their physical and mental health. Methods: A questionnaire was administered, containing questions about participants’ background information and the following scales: the Job Satisfaction Survey, the Rosenberg Self-Esteem Scale, the Physical and Mental Health Scales (SF12), and the Ivens Scale in the Adapted Version for Teachers: School Children’s Happiness Inventory (SCHI). The participants were 300 primary and middle school teachers from the Indian State of Kerala. Results: Job satisfaction fully mediates between both happiness and self-esteem, and health in teachers. Conclusion: Work is a relevant domain to promote teachers’ happiness and self-esteem, and their health, through job satisfaction.